Mangrove Litter Production in the Teluk Buo, Bungus Sub-district, Teluk Kabung District, Padang, Sumatera Barat Province - Eva Nurjannah Simamora; Adriman '; M Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Teluk Buo mangrove forest is one of tourist destination in the Sumatera Barat Province. Thet forest, however mostly inhabit by seedlings, while trees are scarce. This condition may affect the mangrove litter production. A research aims to understand mangrove litter production in Teluk Buo was conducted on February 2017. The litter was collected using a net (1x1 m) that was set under the canopy, around 2 meters height from the forest floor. The net was set for 21 days and once/ 7 days, the litter was removed. The collected litter was then dried in the oven 105OC for 24 hours. The leaves, propaguls and twigs were separated and weighed. Total mangrove litter production average was 7.87 g/m2/day. The leaf is the main component of the litter in mangrove (7.03 g/m2/day), followed by propagules (0.26 g/m2/day) and twigs (0.58 g/m2/day).Keywords: leaves, forest, canopy